التسويق الالكتروني في ظل الأزمة الصحية كوفيد 19 في الجزائر "عينة من ولاية سوق أهراس" - محمد أمين رزايقية; مراد سديرة (My University, 2021)
This study aims to shed light on the extent to which the COVID-19 health crisis has contributed to relying on e-marketing and its impact on it, and by applying social distancing measures during the quarantine period. E-marketing has affected consumer behavior during this period, as it provides many opportunities for the consumer, and now many people prefer it over normal marketing, through which the consumer can shop remotely and order what he wants over the Internet without having to leave his home and break the health protocol, Just by clicking on their computer, or their electronic tablet, they buy whatever products they want and they secure their lives. .................................................................. تهدف هىذه الدراسة الى تسليط الضوء على مدى مساهمة الأزمة الصحية كوفيد 19 على الاعتماد على التسويق الالكتروني و تأثيرها عليه، و بتطبيق إجراءات التباعد الاجتماعي خلال فترة الحجر الصحي التسويق الالكتروني بأهمية كبيرة سواء عند المؤسسات الربحية بمختلف أنواعها و مجالاتها، و كذا عند المستهلك. وقد أثر التسويق الالكتروني على سلوك المستهلك خلال هذه الفترة، حيث يتيح فرص عديدة للمستهلك، و حاليا فإن الكثير من الناس يفضلونه على التسويق العادي، فمن خلاله يستطيع المستهلك التسوق عن بعد و طلب ما يريده عبر الانترنت دون الحاجة لمغادرة منزله و كسر البروتوكول الصحي، فقط بمجرد النقر على حاسبهم الشخصي ،أو لوحتهم الالكترونية، يشترون ما يشاءون من منتجات و هم بذلك يؤمنون حياتهم.